AN ANALYSIS OF ILLOCUTIONARY SPEECH ACT TYPES AND CONTEXT OF USED IN CINDERELLA MOVIE; A PRAGMATIC APPROACH - Mardian, Fera; Suhardianto, Suhardianto (LPPM Universitas Putera Batam, 2019)
Communication is important things for human being without communication people cannot share express their ideas, feelings, and information to each others. Langauge use to connect to human life by the conversation.This research analyzed about illocutionary act that find in Cinderella’s movie in 2015. This thesis analyzed what are types of illocutionary act and what are the context used in Cinderella’s movie. In this research, the researcher analyzed the types and context of illocutionary act that used in the movie. Illocutionary act consist of five types: assertive, directive, commissive, expressive, and declaration. This research is a descriptive qualitative. The technique of collecting data from this reseacrh is by observation method. The steps of analyzing the data, the researcher download and watching the movie. Then, the researcher take a note to write the utterance in the movie scripts and the researcher analyzed and caterogized the utterance that related to the types and context of illocutionary act. The data use informal way, which just by the words. The results of the data analysis are 20 there are 8 utterances that find of Assertive, 4 utterances of Commissive, 5 utterances of Directive, 3 utterances of expressive, and in the last is Declarative there is no declarative found in the data analysis.